Effects of Resistant Starch Interventions on Metabolic Biomarkers in Pre-Diabetes and Diabetes Adults - Rashed, Aswir Abd; Saparuddin, Fatin; Rathi, Devi-Nair Gunasegavan; Nasir, Nur Najihah Mohd; Lokman, Ezarul Faradianna (Frontiers in Nutrition, 2022)
Simple lifestyle changes can prevent or delay the onset of type 2 diabetes mellitus (T2DM). In addition to maintaining a physically active way of life, the diet has become one of the bases in managing TD2M. Due to many studies linking the ability of resistant starch (RS) to a substantial role in enhancing the nutritional quality of food and disease prevention, the challenge of incorporating RS into the diet and increasing its intake remains. Therefore, we conducted this review to assess the potential benefits of RS on metabolic biomarkers in prediabetes and diabetes adults based on available intervention studies over the last decade. Based on the conducted review, we observed that RS intake correlates directly to minimize possible effects through different mechanisms for better control of prediabetic and diabetic conditions. In most studies, significant changes were evident in the postprandial glucose and insulin incremental area under the curve (iAUC). Comparative evaluation of RS consumption and control groups also showed differences with inflammatory markers such as TNF-α, IL-1β, MCP-1 and E-selectin. Only RS2 and RS3 were extensively investigated and widely reported among the five reported RS types. However, a proper comparison and conclusion are deemed inappropriate considering the variations observed with the study duration, sample size, subjects and their metabolic conditions, intervention doses, and the intervention base products. In conclusion, this result provides interesting insights into the potential use of RS as part of a sustainable diet in diabetes management and should be further explored in terms of the mechanism involved.